SAHABAT PERPUSTAKAAN DIGITAL: PENINGKATAN KEMITRAAN SEKOLAH DAN MASYARAKAT DALAM PENGEMBANGAN LITERASI - Rudy Setiawan; Elita Mega Selvia Wijaya (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
This community service program aims to increase partnerships between schools and the community in literacy development through extracurricular activities and the construction of digital libraries at SMAS Islam Diponegoro Wagir. This program is a response to the condition of partner schools that face limitations in reading collections, suboptimal library management, and lack of community participation in supporting literacy culture. Activities are carried out through problem identification, planning, implementation, and evaluation of results. Various extracurricular-based literacy activities and the provision of digital reading access are carried out to improve students' literacy skills. The development of digital libraries using the Google Sites platform makes it easier for students to access learning resources. In addition, the involvement of parents and the community is also increased through collaboration in literacy activities. The results show an increase in students' interest in reading, active literacy activities in schools, and the emergence of community support for literacy culture. This program has been proven to be able to strengthen the school literacy ecosystem with a participatory and sustainable approach.